1993
DOI: 10.1111/j.1464-0597.1993.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Priority Patterns among Managerial and Professional Women

Abstract: Cette recherche examina les antecedents et les condquences des modtles de prioritt dans la carritre professionnelle des femmes cadres. Sept cent quatre vingt douze femmes expliqukrent leur attachement A la carritre en premier, ou A la carriere modifike en fonction de la famille. ou A la camtre orientee en fonction de la famille. L'kchantillon dans son ensemble etait plus oriente vers carriere et famille plut6t que vers camtre en premier. Des variables demographiques et situationnelles furent mises en correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 6 publications
10
82
0
3
Order By: Relevance
“…Therefore, if, on the supply side, women gained more expertise and adopted more male patterns of career planning (person centred approach) and if, on the demand side, this was buttressed by a commitment to equal opportunities in the workplace (corporate practices approach), then their career progress would be enhanced. Still (1992) for example has referred to the need for women to gain the right qualifications and skills and Burke and McKeen (1994) argue that many women, in tacit acceptance of this approach, embark of higher level qualifications such as an MBA in order to try to overcome some of the barriers they face in their careers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, if, on the supply side, women gained more expertise and adopted more male patterns of career planning (person centred approach) and if, on the demand side, this was buttressed by a commitment to equal opportunities in the workplace (corporate practices approach), then their career progress would be enhanced. Still (1992) for example has referred to the need for women to gain the right qualifications and skills and Burke and McKeen (1994) argue that many women, in tacit acceptance of this approach, embark of higher level qualifications such as an MBA in order to try to overcome some of the barriers they face in their careers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the one hand, research has shown that women attempting to combine professional or managerial careers with family commitments report less job satisfaction, less job involvement, and less career satisfaction than women who chiefly emphasized their careers (Burke & McKeen, 1993). Kirchmeyer (2002) found that having children is associated with reduced perceptions of career success for female managers, and employees experiencing strong difficulties balancing competing work and home responsibilities have also reported lower levels of subjective career success (Peluchette, 1993).…”
Section: Career Satisfaction and Subjective Career Successmentioning
confidence: 99%
“…Women's voice research was thus concerned with highlighting gender difference in areas such as career progress and career orientation (e.g. Alban- Metcalfe, 1984;Burke and McKeen, 1994;Burke, Rothstein and Bristor, 1995;Davidson and Cooper, 1992;Gutek and Larwood, 1987;Hammond and Holton, 1991;Nicholson and West, 1988;Rosen, Miguel and Pierce, 1989;Tharenou, Latimer and Conroy, 1994), experience of career barriers (e.g. Adler, 1993;Coe, 1992;Hansard Society Commission, 1990;Marshall, 1984;Oakley, 2000;Povall, 1984) and leadership behaviours (Davidson and Cooper, 1987;Donnell and Hall, 1980;Ferrario, 1991;Loden, 1985;Rosener, 1990) with the explicit aim of achieving 'gender justice' through the removal of gender-based barriers to career success.…”
Section: Women's Voice Literaturementioning
confidence: 99%